Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Given the function [tex]\( f(x) = \sqrt{x+3} - 2 \)[/tex], calculate the average rate of change between [tex]\( x = 6 \)[/tex] and [tex]\( x = 13 \)[/tex].

A. [tex]\(\frac{1}{7}\)[/tex]
B. [tex]\(-\frac{1}{7}\)[/tex]
C. 7
D. -7


Sagot :

To solve this problem, let's break it down into a few steps.

1. Understanding the function:
Given the function [tex]\( f(x) = \sqrt{x + 3} - 2 \)[/tex].

2. Calculate the values of the function at the given points:
- For [tex]\( x = 6 \)[/tex]:
[tex]\[ f(6) = \sqrt{6 + 3} - 2 = \sqrt{9} - 2 = 3 - 2 = 1 \][/tex]
- For [tex]\( x = 13 \)[/tex]:
[tex]\[ f(13) = \sqrt{13 + 3} - 2 = \sqrt{16} - 2 = 4 - 2 = 2 \][/tex]

3. Plug in the function values into the average rate of change formula:
The average rate of change of a function [tex]\( f(x) \)[/tex] between [tex]\( x = a \)[/tex] and [tex]\( x = b \)[/tex] is given by:
[tex]\[ \text{Average rate of change} = \frac{f(b) - f(a)}{b - a} \][/tex]
Here, [tex]\( a = 6 \)[/tex] and [tex]\( b = 13 \)[/tex].

Substitute [tex]\( f(6) = 1 \)[/tex] and [tex]\( f(13) = 2 \)[/tex] into the formula:
[tex]\[ \text{Average rate of change} = \frac{f(13) - f(6)}{13 - 6} = \frac{2 - 1}{13 - 6} = \frac{1}{7} \][/tex]

4. Match the result with the given options:

The average rate of change is [tex]\(\frac{1}{7}\)[/tex], which matches choice:
[tex]\[ \frac{1}{7} \][/tex]

Thus, the answer is:
[tex]\[ \boxed{\frac{1}{7}} \][/tex]